2021
DOI: 10.3390/cancers13194818
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Double-Strand Breaks: The Role of DNA Repair Proteins in Cancer Stem-Cell Regulation

Abstract: Cancer stem cells (CSCs) are pluripotent and highly tumorigenic cells that can re-populate a tumor and cause relapses even after initially successful therapy. As with tissue stem cells, CSCs possess enhanced DNA repair mechanisms. An active DNA damage response alleviates the increased oxidative and replicative stress and leads to therapy resistance. On the other hand, mutations in DNA repair genes cause genomic instability, therefore driving tumor evolution and developing highly aggressive CSC phenotypes. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 252 publications
(403 reference statements)
0
11
0
Order By: Relevance
“…CSCs can undergo extensive metabolic reprogramming [ 47 ], showing rapid DNA damage repair [ 48 ] and enhanced cancer drug resistance [ 49 ]. DNA repair proteins play crucial roles in CSC maintenance and adaptation to replication and oxidative stress [ 50 ]. Among them, testis-expressed protein 264 (TEX264) [ 51 ] and forkhead box M1 (FOXM1) [ 52 ] are involved in DNA repair response.…”
Section: Resultsmentioning
confidence: 99%
“…CSCs can undergo extensive metabolic reprogramming [ 47 ], showing rapid DNA damage repair [ 48 ] and enhanced cancer drug resistance [ 49 ]. DNA repair proteins play crucial roles in CSC maintenance and adaptation to replication and oxidative stress [ 50 ]. Among them, testis-expressed protein 264 (TEX264) [ 51 ] and forkhead box M1 (FOXM1) [ 52 ] are involved in DNA repair response.…”
Section: Resultsmentioning
confidence: 99%
“…These molecules are detected by immune cells, resulting in the activation of the adaptive immune system and the release of pro-inflammatory cytokines and chemokines [ 35 , 36 ]. Additionally, several reports have shown that radiation-induced accumulation of cytosolic DNA triggers activation of cyclic GMP-AMP synthase-stimulator of interferon genes (cGAS/STING) pathway, one of the critical mechanisms activating antitumor immune response [ 37 , 38 , 39 , 40 , 41 ]. The immunomodulatory effects of radiotherapy open up an avenue for radioimmunotherapy combination treatment.…”
Section: Introductionmentioning
confidence: 99%
“…With high plasticity from a dormant status to highly proliferative, depending on the tumor microenvironment, [6,7], activation of DNA repair systems [8][9][10], and modulation of autophagic and apoptotic cell death [11][12][13], CSC are referred to as the source of chemoresistance. However, the exact mechanism of resistance is not clear and understanding mechanisms underlying drug resistance and identifying novel modalities of therapy has remained as the major focus of research in the field [14].…”
Section: Introductionmentioning
confidence: 99%
“…Chemoresistance in glioma cells is a complex process that involves multiple factors including dysregulation of programmed cell death pathways [3], presence of tumor residues that contain cancer stem cell (CSC) populations [4, 5], and the activation of DNA repair system. With high plasticity from a dormant status to highly proliferative, depending on the tumor microenvironment, [6, 7], activation of DNA repair systems [810], and modulation of autophagic and apoptotic cell death [1113], CSC are referred to as the source of chemoresistance. However, the exact mechanism of resistance is not clear and understanding mechanisms underlying drug resistance and identifying novel modalities of therapy has remained as the major focus of research in the field [14].…”
Section: Introductionmentioning
confidence: 99%